Konsep Model â€œEmpowerment Learningâ€ Pada Pendidikan Tinggi Keislaman Dalam Perspektif Pedagogik Kritis - Saiful Hadi; Zulvy Alivia Hanim (TADRIS: Jurnal Pendidikan Islam, 2019)
This article attempts to initiate the change of learning models that occur in the Islamic educational environment. By initiating the model of learning-oriented in order to improve the capacity of graduates who are able to apply the scientific fields of Islamic studies in daily life in accordance with the demands and changes in the model of social life by mastering the religious dogmas becomes a source of value that can be applied in solving problems of mental spiritual life of the society. The dynamics of changes that occur in Indonesian Islamic society are influenced by the success of educational change Islamic Higher Education is one of the strategic elements that massively try to make the process of change through the determined educational program. Trough the process of learning, itÂ  that can provide the space of thinking, and the space of understanding for each individual who learns to critically resolve the phenomena of life to a constructive lifestyle with a spiritual foundation.Â Keywords: empowerment learning, PTKI, critical pedagogy